Optimizing winter maize production in Bihar: Addressing the yield gaps through practical insights, strategies, and evidenced yield improvements - Jat, Raj Kumar; Durgude, Shubham Anil (Indian Farming, 2025)
Winter maize has emerged as a key driver of food security and rural prosperity in Bihar, yet its full potential often goes untapped due to a mix of climatic unpredictability, soil-related constraints, and conventional farming approaches. Based on extensive on-farm experience across major maize growing districts, this article highlights practical field-level strategies that have proven effective under real farming conditions. From optimizing sowing time and planting methods to choosing suitable hybrids and improving water and nutrient use, several factors have been identified that distinguish higher-yielding fields from others. The insights presented here aim to guide farmers towards more productive, resilient, and sustainable maize cultivation practices.